"Divided against itself"?: individual maxims and the redaction of Q - Howes, Llewellyn (Acta theologica, 2015)
In his analysis, Kloppenborg (1987) identified a number of logia in the main redaction that were more proverbial than prophetic in nature. This article considers the possibility that these sayings originally formed part of Q¹, but were added to Q² by the main redactor during the redactional process. It also explores the possibility that the main redactor not only inserted and interpolated prophetic material into Q¹, but also transformed original wisdom sayings into prophetic Q² material.